2021
DOI: 10.15407/surface.2021.13.182
|View full text |Cite
|
Sign up to set email alerts
|

Basalt fiber based biocide materials

Abstract: It has long been known that materials containing cellulose fibers in their composition are destroyed by molds, microorganisms, actinomycetes, which use cellulose as a carbon source. Different fibrous materials to varying degrees (but always) are affected by molds. It is known that linseed and cotton types of paper are affected by the smallest number of fungi, and sulphate ones by the largest. The most biostable is cotton paper, the composition of which contains chalk in a sufficiently large amount. The observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…1, a). Shevchenko in his work on the topic "Creation of basalt fiber production technology based on raw material minerals of the Republic of Uzbekistan" [3] showed that concentration intervals based on basalt, limestone, phosphorous components obey the fundamental laws of the formation of difficult-to-dissolve eutectics in silicate systems, the quantitative change of solids when adding additives and found that there is a direct relationship between the viscosity of the solution. In addition, he justified the possibility of using the mineral raw materials of the Republic of Uzbekistan for the industrial production of high-quality basalt fiber.…”
Section: Introductionmentioning
confidence: 99%
“…1, a). Shevchenko in his work on the topic "Creation of basalt fiber production technology based on raw material minerals of the Republic of Uzbekistan" [3] showed that concentration intervals based on basalt, limestone, phosphorous components obey the fundamental laws of the formation of difficult-to-dissolve eutectics in silicate systems, the quantitative change of solids when adding additives and found that there is a direct relationship between the viscosity of the solution. In addition, he justified the possibility of using the mineral raw materials of the Republic of Uzbekistan for the industrial production of high-quality basalt fiber.…”
Section: Introductionmentioning
confidence: 99%